Communication for Sustainability in the Ecuadorian Amazon: the Case of the YAsuní Biosphere Reserve - Duque-Rengel, Vanessa; Heredia-Rengifo, Marco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Communication for sustainability is essential in rural livelihoods, due to the syn- ergies in decision-making processes. This study proposes: 1) to characterize the sociodemographic and productive conditions at the household level of indigenous and migrant settlers in the Yasuní Biosphere Reserve and 2) to analyze communi- cation strategies that contribute to sustainable development. 40 household surveys were conducted, and 5 in-depth interviews with experts in strategic communi- cation and sustainability. It was evidenced: high productive diversity; limited marketing and promotion capacity; and strategies and strategic actors such as for sustainability.